POTENSI EKSTRAK Cymbopogon citratus DC. DAN Mucuna bracteata DC. TERHADAP PENGHAMBATAN PERKECAMBAHAN DAN PERTUMBUHAN GULMA Borreria alata (Aublet) DC. - Dewi Yuni Safitri; Siti Fatonah; Herman ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
One of the environmentally friendly alternative in controlling weed is by using organic herbicides. The potential plant as organic herbicides such as Cymbopogon citratus and Mucuna bracteata, contain essential oils and allelopat. This research aimed to determine the extract influence and the best concentration of C. Citratus and M. bracteata in inhibiting the germination and growth of Borreria alata. This research used a randomized design with seven treatments i.e. control (0%), 20%, 40%, 60% C. Citratus extract and 20%, 40%, 60% M. bracteata extract. The observed data were analized using ANOVA and if significantly different followed by DMRT. The results showed that all treatments of the extract decreased the germination and growth of P. conjugatum and Borreria alata. The best extract was 40% and 60% M. bracteata that inhibit the germination and growth of B. alata.